Characterization of the blood sucking arthropods in cave of Gabon and their involvement in the infectious agents transmission - (:unkn) unknown (My University, 2016)
The man's ecological mark on natural forest environments of central Africa has been increasing in recent decades, and only few natural areas remain non exploited yet. Thus, even supposedly hostile environments such as caves meet the primary needs of surrounding populations (hunting, fishing, shamanic practices), or economical needs (mining and ecotourism). That anthropization is likely to increase the exposure of human populations to multiple infectious agents carried by cave fauna. The presence of wild or domestic animals in the surroundings of caves also increase that risk. Among these infectious agents, some can be transmitted by direct contact with animal reservoirs, whereas others may require the involvement of blood-sucking insects. The role of these insects in the epidemiology of many pathogens is well known in Africa, particularly in epigeic environments, but remains largely investigated in caves. In this thesis work, we proposed to address that issue. In six caves of Gabon we firstly explored the diversity of blood-sucking Diptera, and we studied temporal dynamics of species assemblages. Secondly, we undertook a molecular screening of haemosporidia, bacteria and viruses using nested PCR and high-throughput sequencing.The work carried out has enable to make a taxonomic inventory of the Diptera fauna of the investigated caves. Our study revealed a significant diversity of the blood-sucking Diptera fauna, accounting for more than 60 percent of blood-sucking Diptera species currently known in Gabon, in all types of areas. Our data showed that the composition of Diptera communities was different from one cave to another, and that Diptera assemblages varied over time according to micro-climate fluctuations within caves. The screening of infectious agents in Diptera collected helped 1) to explore the parasitic, viral and bacterial diversity they host, and 2) to assess their involvement in transmission.
Keywords: African Research